2008
DOI: 10.1088/0953-8984/20/04/045203
|View full text |Cite
|
Sign up to set email alerts
|

Electron Raman scattering in semiconductor quantum wire in an external magnetic field

Abstract: The differential cross-section for an electron Raman scattering process in a semiconductor quantum wire in the presence of an external magnetic field perpendicular to the plane of confinement is calculated. We assume a single parabolic conduction band. The emission spectra for different scattering configurations and the selection rules for the processes are studied. Singularities in the spectra are found and interpreted. The electron Raman scattering studied here can be used to provide direct information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 19 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…Here Ĥρ is the Hamiltonian operator for the radiation field, in the dipole approximation, with frequency ω ρ and polarization unit vector 𝑒 ρ , [42] while |i and | f are the initial and the final states with energies E i and E f , respectively; and |a and |b are the intermediate states with energies E a and E b , whose lifetimes are Γ a and Γ b . In this case, we have two possibilities: [42] (i) the electron absorbs the incident photon and later emits the secondary radiation photon, which is represented by the first term of Eq. ( 5); (ii) the electron emits the secondary radiation photon and later absorbs the incident photon which is represented by the second term of Eq.…”
Section: Raman Cross-sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here Ĥρ is the Hamiltonian operator for the radiation field, in the dipole approximation, with frequency ω ρ and polarization unit vector 𝑒 ρ , [42] while |i and | f are the initial and the final states with energies E i and E f , respectively; and |a and |b are the intermediate states with energies E a and E b , whose lifetimes are Γ a and Γ b . In this case, we have two possibilities: [42] (i) the electron absorbs the incident photon and later emits the secondary radiation photon, which is represented by the first term of Eq. ( 5); (ii) the electron emits the secondary radiation photon and later absorbs the incident photon which is represented by the second term of Eq.…”
Section: Raman Cross-sectionmentioning
confidence: 99%
“…The effect of reduced dimensionality on the free carrier absorption and the selection rules for intersub-band transition has been discussed in Ref. [42], and there it is shown that the ERS can only take place in the confinement direction, then…”
Section: Raman Cross-sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DCS of electron Raman scattering in a volume V per unit solid angle dΩ for the incident light with the frequency ω l and the scattered light with the frequency ω s is given by [69] …”
Section: Raman Cross-sectionmentioning
confidence: 99%
“…There exist many experimental studies which concerning the Raman scattering in nanostructures [56,57,58,59,60,61,62]. A great number of theoretical works has also been devoted to interpret the experimental results through the calculation of the differential cross-section (DCS) for the electron-Raman scattering (ERS) [63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82]. Ismailov and Mehdiyev [76] have investigated the effects of the dot size and the external magnetic field on the ERS in a cylindrical QD.…”
Section: Introductionmentioning
confidence: 99%